Parents and Children During the COVID-19 Quarantine Process: Experiences From Turkey and China - TORAN, MEHMET; Sak, Ramazan; Xu, Yuwei; Sahin-Sak, Ikbal Tuba; Yu, Yun (Sage Publications Inc., 2021)
This paper reports Turkish and Chinese parents' experiences with their 3-6 year-old children during the COVID-19 quarantine process. Thirteen Turkish and 11 Chinese parents participated in a study that employed semi-structured interviews to examine participant self-perceived experiences. Findings show that the study revealed many commonalities in the experiences of Turkish and Chinese parents with their children during the COVID-19 quarantine process. Cultural differences between parents did not appear to significantly reflect the responses of parents during this extraordinary period. Parents mostly described difficulties with home quarantine. Most parents stated that their daily schedule and routines had changed as a result of home quarantine. Parents also said that they were unaware of their children's developmental progress and the extent to which their children had grown up before the quarantine. Parents shared both positive and negative experiences during the process. Since the quarantine process is an extraordinary experience for all family members, parents should be encouraged to put those positive experiences and acquisitions into their future life.
Keywords: Covid-19; Experience; Parents; Preschool Children; Quarantine